Genetic structure of the threatened Phaedranassa schizantha (Amaryllidaceae). (23rd June 2016) - Oleas, Nora H.; Meerow, Alan W.; Francisco‐Ortega, Javier
Abstract : Phaedranassa schizantha (Amaryllidaceae) is an endangered species endemic to Ecuador and two varieties have been described: P. schizantha var. schizantha and P. schizantha var. ignea . We assessed population genetic structure and demographic patterns in 11 populations across the range of the species using 13 microsatellite loci. Our data show that genetic diversity was generally lower in the southern part of the range and was especially low in populations closest to cities. We found significant population differentiation ( F ST = 0.14, D EST = 0.34) and evidence of a genetic bottleneck. Genetic variation did not show isolation by distance. Instead, results suggest genetic barriers around two main cities. Bayesian analysis identified two genetic groups, neither of which represents either of the two varieties previously recognized. Coalescent analysis indicates a relatively recent colonization pattern between the two genetic groups (< 3000 generations). Conservation efforts need to be taken to facilitate genetic exchange between the groups, especially between locations that seem to be genetically isolated.